Effects of Fertility Behaviors on Depression Among the Elderly: Empirical Evidence From China - Hu, Zhen; Wu, Yuanyang; Yang, Hualei; Xie, Lin; Zhang, Anqi; Lin, Xueyu; Nie, Yafeng; Zhang, Xiaoyu (Frontiers in Public Health, 2021)
Background: Increased population aging is associated with increased incidence of depression among the elderly. Existing studies have shown that ill-advised fertility behaviors during their youth also affect the health of the elderly. However, insufficient attention has been paid to depression among elderly in China. This paper focuses on how fertility behaviors affect senile depression among parents by examining the heterogeneity of such effects and tests the applicability of existing theoretical findings in a Chinese sample. Methods: The effects of fertility behaviors on depression among the elderly were investigated using the China Health and Retirement Longitudinal Study (CHARLS), a nationally representative dataset. The effects of early-age fertility behaviors on the degree of depression among the elderly were investigated using ordinary least squares and ordered probit models that adjusted for demographic and socioeconomic factors. Results: 1) The age of first childbirth, childbearing period, and number of births were significantly and positively correlated with the degree of depression among the elderly (particularly rural persons aged 50 to 70 and older womens). 2) Elderly persons with sons had no better mental health status than those without sons, thus indicating the inapplicability of the traditional concept of “more sons are equal to more happiness” to the actual mental health situation of the elderly in China today. Conclusion: Overall, multiple, late, and boy-oriented childbearing and overly long childbearing periods had negative effects on mental health among Chinese elderly persons. This study tested the applicability of existing theoretical inferences and empirical conclusions in China, thereby further expanding the current literature regarding the effects of fertility behaviors on depression among the elderly.